2006
DOI: 10.5642/aliso.20062201.08
|View full text |Cite
|
Sign up to set email alerts
|

The Fossil Record of Basal Monocots

Abstract: The fossil record of basal monocots (Acorales and Alismatales) extends back to the Cretaceous in the Northern Hemisphere. While many fossils were originally assigned to these basal groups, rigorous paleobotanical studies show many of them to be misidentified. Acarus fossils have been reliably reported from the Eocene while those of Alismatales extend back to the early Cretaceous. The fossil record of basal monocots is usually represented by leaves, fruits, and seeds; however, some localities preserve stems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Using eight reference fossils, Bremer (2000) estimated the age of the split between Acorus and all other monocot lineages at 134 Mya. Later, it has been shown that one of Bremer's reference fossils (fossil B) is not a Pistia of Araceae as assumed, but a different, unknown plant (Stockey, 2003). Recalculation of the mean change rates used by Bremer, and recalibration without that fossil gives, however, the same result.…”
Section: Methodsmentioning
confidence: 99%
“…Using eight reference fossils, Bremer (2000) estimated the age of the split between Acorus and all other monocot lineages at 134 Mya. Later, it has been shown that one of Bremer's reference fossils (fossil B) is not a Pistia of Araceae as assumed, but a different, unknown plant (Stockey, 2003). Recalculation of the mean change rates used by Bremer, and recalibration without that fossil gives, however, the same result.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION-Affinities of the fossil flowers-These fossil flowers have previously been thought to represent an undescribed alismatid taxon (Currah and Stockey, 1991;Stockey, 1994Stockey, , 2001Pigg and Stockey, 1996;Stockey, 2004, 2005). Morphologically, the fossil flowers resemble some families of Alismatales (particularly Aponogetonaceae, Juncaginaceae, and Potamogetonaceae) and Piperales (Saururaceae), all of which have minute flowers borne on spikes (or racemes).…”
Section: Stratigraphy and Age-princeton Group Allenby Fm; Middle Eomentioning
confidence: 99%
“…No fossil vegetative or pollen remains have been firmly placed in the family Saururaceae. However, we recently recognized that fossil flowers from the Middle Eocene Princeton Chert, previously thought to have affinities to Alismatales (Currah and Stockey, 1991;Stockey, 1994Stockey, , 2001Pigg and Stockey, 1996;Stockey, 2004, 2005), have many similarities to saururaceous flowers. Here, we describe this flower type and demonstrate that while these fossil flowers are similar to certain alismatids, floral and inflorescence structure and anther contents suggest that this flower type is related to Saururaceae (Piperales).…”
mentioning
confidence: 99%
“…The evolution of the monocots have been a topic of considerable interest in recent years, and several authors have looked to the fossil record for information about the evolution and phylogeny of this group (e.g., Stockey 2006;Smith 2013). Among the most noteworthy contributions of the Princeton chert plants are several reports of anatomically preserved monocots.…”
Section: Monocotsmentioning
confidence: 99%